The Securities and Exchange Commission and the Financial Accounting Standards Board: Regulation Through Veto-Based Delegation - Melumad, Nahum D.; Shibano, Toshiyuki (Journal of Accounting Research, 1994)
Nahum D. Melumad, Toshiyuki Shibano, The Securities and Exchange Commission and the Financial Accounting Standards Board: Regulation Through Veto-Based Delegation, Journal of Accounting Research, Vol. 32, No. 1 (Spring, 1994), pp. 1-37